Educators' Experiences Teaching Literary Journalism in Brazil: A Comparative Study with International Community (Intercom - Brazilian Journal of Communication Sciences, 2024)
Beginning in 2011, the teaching of literary journalism around the world has been investigated annually by surveying educators of the field (LEWIS; HANC, 2018). From 2018 on, this long-term study has highlighted Brazilian scholarship differences, similarities, contributions, and challenges. The purpose of this article is to compare Brazilian findings in contrast with ones of an international community that includes twenty countries across five continents. These results may help understanding how the teaching of literary journalism contributes to students learning and further developing transferable skills (e.g., NEELY; LEWIS, 2020), and to future lines of inquiry, so that the discipline of literary journalism may continue on its path of coalescence and achieving its potential.
Keywords: : Teaching of literary journalism; Educators; Research in Literary Journalism; Brazil